Patterns of object play behaviour and its functional implications in free-flying common ravens - Awani Bapat; Anna E. Kempf; Salomé Friry; Palmyre H. Boucherie; Thomas Bugnyar (Scientific Reports)
Abstract Object play has been proposed to provide individuals with information about their environment, facilitating foraging skills and tool use. In species where object play co-occurs with locomotor or social play, it may have additional functional implications, such as facilitating the evaluation of peers or forming social bonds. For instance, ravens judge others’ competitiveness via play caching and engage in social play by exchanging objects. However, most raven studies were conducted on a restricted number of individuals and under controlled captive settings. To validate these findings and to gauge the functional scope of object play under field conditions, we investigated the patterns and characteristics of object play in individually marked free-flying ravens in the Austrian Alps. Using two large data sets, we show a decrease in object play with age and a preference for playing longer with novel objects, supporting findings from captivity. We also find adults occasionally playing with objects and no difference in the duration of social or non-social object play bouts across age classes. Taken together, our findings are in line with the assumption that raven object play likely has more than one function and serves to gain information about the individual’s physical and social environment.